CONDUCTING CROSS-CULTURAL ONLINE AUDIENCE RESEARCH WITH TWO GENERATIONS: METHODOLOGICAL EXPERIENCES AND REFLECTIONS FROM THE PANDEMIC CONTEXT - Bolin, Göran; Figueiras, Rita; Kalmus, Veronika (AoIR Selected Papers of Internet Research, 2023)
This paper discusses methodological, ethical, and empirical problematics related to forced changes in the research design of a comparative project during the Covid-19 pandemic, and its wider implications for future online audience research. The larger project aims to understand media users’ attitudes towards corporate and state surveillance in countries with different historical surveillance regimes: Estonia, Portugal, and Sweden. In a mixed-methods design, comprising an online survey and focus groups (FGs), we sampled participants from two generational cohorts: born in 1946-1953 and in 1988-1995. In each country, we planned six face-to-face FGs with people from these generational cohorts, divided into three gender-balanced groups with different profiles: higher education; mixed education, living in small cities/countryside; secondary education. The paper discusses the challenges of conducing FGs online, namely the effects of the technological interface on the group size and interaction, the importance of digital skills, and ethics-related considerations. Although we encountered cultural differences between the three countries, our main methodological lessons and suggestions for further audience studies center on the need to consider the subtle facets of inter-generational differences when planning online research. As we witnessed, not all barriers were rooted in access to technology and connectivity. The level of digital skills and self-confidence in use also played a role in participants’ possibilities and willingness for taking part in online research. Further research is needed to explore how age and online methods intersect, and the role online settings play, in the experience of focus group and interview participants with various social backgrounds.